Effect of Various Culture Media on Mouse 2-cell Development - Tocharus, Chainarong; Tocharus, Jiraporn (Asian Health, Science and Technology Reports, 2005)
Developing a culture system for embryos has important biotechnological implications due to the potential to produce large number of preimplantation embryos. As an initial step toward accomplishing this long-term goal, a study was conducted to determine the effects of culture media on embryo development in vitro. These studies were designed to examine the development of mouse embryos from the 2-cell to the hatched-blastocyst stages in the presence of various co-culture systems comparing with culture medium alone. In vivo fertilized 2-cell embryos were surgically collected from superovulated mice 48 hrs after mating. Embryo were randomly divided into 7 culture groups as follows: culture with TCM199+BSA, commercial 1 or commercial 2; co-culture with bovine, porcine, swamp buffalo oviduct epithelial cells or mouse granulosa cells. After 72 hrs in culture, the proportion of 2-cell embryos developed to blastocyst in commercial 2 or swamp buffalo oviductal cells were significantly higher than other culture media or co-culture. The embryos developed to hatched blastocyst were significantly higher in commercial 2 medium than swamp buffalo. Physicochemical analysis indicated that the substances in all culture media were predominantly detected at 66 kDa. These results revealed that embryos cultured in medium alone were more effective in supporting mouse embryo development than the embryos cultured in co-culture system. Therefore, the available commercial culture medium has provided a new in vitro model for embryo production research in numerous species of animals.